Oil Price Developments Drivers, Economic Consequences and Policy Responses - Brook, Anne-Marie (OECD Publishing, 2004)
This paper analyses the factors influencing the price of oil and its likely evolution over the next quarter century. It begins by investigating the fundamental forces shaping long-term oil price developments, highlighting the importance of growth-led demand for oil, particularly that emanating from fast-growing, energy-intensive developing countries, and the implications of increasingly geographically concentrated oil reserves. The paper presents oil price projections to 2030 and examines the sensitivity of the projections to the assumptions about growth and non-OPEC supply. While certain combinations of factors could lead to a significantly higher oil price, the projections also suggest that the optimal strategy of resource-rich oil producers would be to prevent it rising too far. The paper then documents short-term influences on the oil price, which peaked at $50 a barrel in 2004, and notes that they have probably led to a significant departure from the long-run equilibrium price ...
Keywords: Economics